2016
DOI: 10.1370/afm.1951
|View full text |Cite|
|
Sign up to set email alerts
|

Inadequate Hydration, BMI, and Obesity Among US Adults: NHANES 2009-2012

Abstract: PURPOSE Improving hydration is a strategy commonly used by clinicians to prevent overeating with the goal of promoting a healthy weight among patients. The relationship between weight status and hydration, however, is unclear. Our objective was to assess the relationship between inadequate hydration and BMI and inadequate hydration and obesity among adults in the United States.METHODS Our study used a nationally representative sample from the National Health and Nutrition Examination Survey (NHANES) 2009 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 25 publications
3
85
1
6
Order By: Relevance
“…Although, research has consistently shown that obesity impacts psychological well-being (Wynne et al, 2014; Chang et al, 2016; Global BMIMC, 2016), a growing body of evidence suggests that psychosocial correlates of obesity may depend on race (Kodjebacheva et al, 2015; Murphy et al, 2015; Kelley et al, 2016), gender (Assari and Caldwell, 2015; Kodjebacheva et al, 2015), and their intersection (Assari and Lankarani, 2015a). Whether race by gender groups differ in the link between sustained obesity and psychosocial distress is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although, research has consistently shown that obesity impacts psychological well-being (Wynne et al, 2014; Chang et al, 2016; Global BMIMC, 2016), a growing body of evidence suggests that psychosocial correlates of obesity may depend on race (Kodjebacheva et al, 2015; Murphy et al, 2015; Kelley et al, 2016), gender (Assari and Caldwell, 2015; Kodjebacheva et al, 2015), and their intersection (Assari and Lankarani, 2015a). Whether race by gender groups differ in the link between sustained obesity and psychosocial distress is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A recent finding by Chang et al [38] showed that the water ought to be better studied in the research of weight management and clinical strategies. An essential nutrient in population’s diet, potable water is usually an inexpensive commodity that is often widely available and accessible by people.…”
Section: Discussionmentioning
confidence: 99%
“…A commonly referenced cut-off for the upper limit of euhydration is a U Osm of 800 mOsm·kg -1 , which has been used in studies of hydration in both children [60][61][62][63] and adults [64,65] . The principle behind the 800 mOsm·kg -1 cut-off has roots in early work by Katz et al [66] , who studied the urine-concentrating capacity of the kidney in hot conditions, and determined that nearly all participants could concentrate their urine up to at least 800 mOsm·kg -1 .…”
Section: Reference Values and Cut-offs: What Is The Target For Optimamentioning
confidence: 99%